Testing growth theories: Time series evidence - Erich Gundlach (Kiel Institute of World Economics (IfW); ZBW – Leibniz Information Centre for Economics, 1992)
Recent time series studies reject the hypothesis of catching up in terms of international per capita incomes as derived from the traditional neoclassical growth model. In turn, they seem to support new theories of economic growth which are capable of explaining persistent international differences in per capita incomes. In this paper I show that this finding is derived under a very restrictive econometric framework. Using a more flexible specification that allows for conditional convergence in per capita incomes and a gradual adjustment over time I derive results that are more favorable for the traditional growth model.
Keywords: C32; O47; 330; development of per capita incomes; cointegration analysis; dynamic specification